Pattern of head injury in motorcycle fatalities - Ong, Beng Beng; Rajam, Krishnan; Lee, Peter (Faculty of Medicine, University of Malaya, 2000)
Head injury contributes to a significant proportion of motorcycle fatalities. The site and pattern of head injury in victims of fatal motorcycle crashes in 1995 were studied retrospectively. The site of impact on the head was determined based on the injuries on the scalp, pattern of skull fractures and injuries of the brain. Of 54 cases, 9 had massive crush injuries. Of the remaining 45 cases, the site of impact was as follows: frontal 21, lateral 14, posterior 4, vertex 1, chin 1 and unascertainable in 4 cases. The majority of injuries occurred on the front and lateral aspects of the skull. Motorcycle helmets are currently tested for impact energy attenuation and penetration test at the vertex. Helmet standards need to take into account site and nature of injury.